P093 Prevalence and incidence of Behçet's Disease in England: A multicentre retrospective observational study. (23rd April 2022) - Chandratre, Priyanka; Chandan, Joht; Hunjan, Manrup; Trudgill, Nigel; Moots, Robert; Fortune, Farida; Situnayake, Rohan Deva
Abstract: Background/Aims: Behçet's disease (BD) is a rare multisystem auto-inflammatory disorder. In England the incidence is estimated between 0.38 per 100, 000 in the population, however, the actual incidence of BD in U.K. is unknown. The prevalence is estimated to be 14.61 (95% CI 13.35-15.88) per 100 000 population in 2017 but the read codes from the THIN network were not validated, thereby potentially causing an overestimate. The study aims to understand the epidemiology of BD in England using primary and secondary data Methods: 1. Annual incidence rate per million person years will be calculated stratified by age, gender and ethnicity 2. Point prevalence will be calculated at the midpoint of the study stratified by age, gender and ethnicity 3. Establish phenotypes and their clusters 4. To identify treatments and outcomes of BD (multi-system morbidity and mortality) 5. The time to diagnosis 6. Equity of access to biologic treatment for BD 7. Identify risk factors for BD. Case ascertainment sources include primary care data from Clinical Practice Research Datalink and secondary care data from the CRPD linked Hospital Episode Statistics. In order to validate the diagnosis of BD in CRPD, data will be triangulated by scrutinising the HES within Sandwell & West Birmingham Hospitals NHS Trust. A list of ICD-10 codes for BD, its complications and treatments needing admission will be used to identify those with BD. The findings will be compared and contrasted to the data from the Birmingham Centre of Excellence using the same codes. The validity of the HES data will be ascertained by comparing proportions of diagnostic and treatment codes within the two data sets. Results: We have conducted a pilot study of the clinical characteristics of those with BD treated at the Birmingham Centre of Excellence between July 2012 and July 2018. The average age of this group was 44 years (SD 11.5). 109 patients were male (36.8%) and 199 (67.2%) were Caucasian. Men presented at a younger age ( 41.9 years compared with 45.2 years for females) and were less likely to experience genital ulceration and musculoskeletal symptoms. 96 (32.4%) patients were currently receiving or had previously received monoclonal antibody therapy. Men on average had a higher Transformed Index score of 7(3-8) (p = 0.0025) and younger age (OR 0.96; 95% CI 0.93-100) and being female (OR 0.30; 95% CI 0.12-0.69) were associated with lower disease activity. Conclusion: To our knowledge, this is the largest population based study of the incidence and prevalence of BD in the UK. It will also be the first study in BD to ascertain diagnostic validity by scrutinising routinely collected clinical data and to describe disease evolution over time in order to better design health services to cater to these needs. Disclosure: P. Chandratre: None. J. Chandan: None. M. Hunjan: None. N. Trudgill: None. R. Moots: None. F. Fortune: None. R. Situnayake: None.